Integrating Service Learning in Higher Education: Developing Civic Responsibility and Practical Skills through Real-World Engagement - Ali Mufron; Dara Vann (Yayasan Adra Karima Hubbi, 2024)
Background: The integration of service learning in higher education has gained significant attention in recent years as an innovative pedagogical approach aimed at fostering civic responsibility and developing practical skills in students. Service learning encourages students to engage with real-world issues while contributing to community development, enhancing their academic and personal growth. Objective: This study aims to explore the impact of integrating service learning into higher education curricula on students’ development of civic responsibility and practical skills, particularly in fostering social awareness, communication, teamwork, and problem-solving abilities. Methods: A mixed-methods approach was employed in this research. Quantitative data were collected through surveys to assess the students’ self-reported changes in civic engagement and skill development. Qualitative data were gathered from focus group discussions to gain insights into students’ experiences and reflections on the service learning activities. Results: The findings indicate that service learning significantly enhanced students’ sense of civic responsibility, critical thinking, and practical skills such as collaboration and communication. Students also reported a stronger commitment to community service and a deeper understanding of social issues. Conclusion: Integrating service learning into higher education not only promotes civic responsibility but also equips students with essential skills for their professional and personal lives. The study recommends further incorporation of service learning in curricula to foster holistic student development.